ADHD, suicidal ideation, depression, anxiety, self-esteem, and alcohol problem in Korean juvenile delinquency. Issue 11 (March 2020) - Chung, Yong-Rae; Hong, Jeong-Won; Kim, Byung-Bae; Kim, Jun-Seong; Noh, Il Suk; Wee, Ji Hee; Kim, Nam Hee; Bae, Sung Man; Lim, Myung Ho
Abstract : Abstract: The purpose of this study is to evaluate the prevalence rates of externalizing symptom, ADHD, as well as internalizing symptoms, depression, anxiety, suicidal ideation, self-esteem, and alcohol problem in Korea juvenile delinquency for the first time in Korea. A case–control study design was used. It also examined the associations with ADHD, suicidal ideation, depression, anxiety, self-esteem, and alcohol problem between the Juvenile Delinquency group and the comparison group in Korea. A series of questionnaires were provided to a total of 251 participants (149 from the juvenile delinquency group and 102 from the comparison group) from October 2015 to December 2015 in Korea. All participants were evaluated using KARS, SSI, BDI, BAI, RSI, and CAGE. This study showed the relationship between ADHD, suicidal ideation, depression, anxiety, self-esteem, and alcohol problem in Korean juvenile delinquency. Also this study showed that ADHD and self-esteem were important factors in predicting juvenile delinquency. Therefore, in order to prevent juvenile delinquency, special attention, and consideration are needed for adolescents with high ADHD or low self-esteem.